Effects of visual training on the reaction time among badminton athletes - Sukmooncharen.A.L Prak, Maruth; Abdullah, Borhannudin; Zulkifly, Nurul Afiqah; Farizan, Noor Hamzani; Samsudin, Shamsulariffin (Universitas Negeri Semarang, 2023)
This study aims to identify the effects of visual training on the reaction time among badminton athletes using two reaction time tests, namely, the Whole-Body Reaction Time (WBRT) and the Finger Reaction Time (FRT). This quasi-experimental study involves 30 badminton athletes (Male = 30, Female = 30). The study involved two groups [treatment group = 30, control group = 30]. The descriptive analysis undertaken shows that the level of reaction time of treatment group for the pre-WBRT test is (M = 0.32, SD = 0.047) and pre-FRT test is (M = 0.48, SD = 0.068). For group control, the pre-WBRT test is (M = 0.33, SD = 0.030) and the pre-FRT test is (M = 0.49, SD = 0.065). On the other hand, the reaction time of treatment group for the post-WBRT test is (M = 0.28, SD = 0.037) and post-FRT test is (M = 0.41, SD = 0.054). Meanwhile, for control group, the post-WBRT test is (M = 0.32, SD = 0.037) and post-FRT test is (M = 0.45, SD = 0.061). Furthermore, for treatment group, there is a significant difference between the pre- and post-WBRT test [t (29) = 8.813, p = .000] and the FRT test [t (29) = 10.329, p = .000]. As for control group, there is also a significant difference between the pre- and post-WBRT test [t (29) = 3.786, p = .001] and the FRT test [t (29) = 4.935, p = .000]. Nevertheless, there is no significant difference between both the two pre-WBRT test group [t (58) = 1.667, p = .101] and the FRT test group [t (58) = 0.546, p = .587]. However, there is a significant difference for both the post-WBRT test group [t (58) = 4.676, p = .000] and the FRT test group [t (58) = 3.056, p = .003]. Overall, this study can help coaches in designing effective training programs which can help to enhance the reaction time level of badminton athletes.